2008
DOI: 10.1590/s0004-28032008000200007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of rectoanal inhibitory reflex in chagasic megacolon

Abstract: BACKGROUND: Rectoanal inhibitory reflex is not always evident in patients with chagasic megacolon. This may be due to insufficient volumes of air used during insufflation for the manometric examination. AIMS: To identify the volume of air necessary to induce rectoanal inhibitory reflex in patients with chagasic megacolon and to observe its prevalence in these individuals. METHODS: Rectoanal inhibitory reflex in 39 patient with chagasic megacolon was studied by means of anorectal manometry using the balloon met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
0
10
1
Order By: Relevance
“…Others have demonstrated an absence of the rectoanal inhibitory reflex in the chagasic megacolon, similar to that in Hirschsprung’s disease 68,69. Alteration of the rectoanal inhibitory reflex in most of the chagasic patients with megacolon was demonstrated by several researchers and can be justified by the destruction of enteric motor innervations 6,11,19,20,22,24,25,68,70. The choice of surgical treatment appears to have the same indication as a solution for constipation in both chagasic and idiopathic megacolon 71,72…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Others have demonstrated an absence of the rectoanal inhibitory reflex in the chagasic megacolon, similar to that in Hirschsprung’s disease 68,69. Alteration of the rectoanal inhibitory reflex in most of the chagasic patients with megacolon was demonstrated by several researchers and can be justified by the destruction of enteric motor innervations 6,11,19,20,22,24,25,68,70. The choice of surgical treatment appears to have the same indication as a solution for constipation in both chagasic and idiopathic megacolon 71,72…”
Section: Discussionmentioning
confidence: 68%
“…In addition, the studies show a lack of relaxation of the internal sphincter of the anus in the chagasic patients 6,11. Others have demonstrated an absence of the rectoanal inhibitory reflex in the chagasic megacolon, similar to that in Hirschsprung’s disease 68,69. Alteration of the rectoanal inhibitory reflex in most of the chagasic patients with megacolon was demonstrated by several researchers and can be justified by the destruction of enteric motor innervations 6,11,19,20,22,24,25,68,70.…”
Section: Discussionmentioning
confidence: 94%
“…18 However, even excluding patients with megarectum (in whom the standard distending balloon may have failed to stimulate sufficiently the rectal pouch), we were unable to find impaired anorectal inhibitory reflex. Others have postulated that an impaired anorectal inhibitory reflex is a pathogenetic factor in chagasic megacolon; but it has been also observed that not all patients with megarectum present an impaired anorectal inhibitory reflex, which suggests that other abnormalities may also play a role in the development of megarectum and megacolon.…”
Section: Discussionmentioning
confidence: 57%
“…A lack of relaxation of the internal anal sphincter and an absence of the rectoanal inhibitory reflex (RAIR) were demonstrated in chronic chagasic patients with megacolon 17 ; this finding could be explained by the presence of aganglionosis. However, in some patients, the absence of the RAIR could be the result of megarectum rather than the expression of a true aganglionosis 18 .…”
Section: From Classical and Recent Morphologic Studies To Manometric mentioning
confidence: 99%